2022
DOI: 10.1007/s00018-022-04185-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroserpin, a crucial regulator for axogenesis, synaptic modelling and cell–cell interactions in the pathophysiology of neurological disease

Abstract: Neuroserpin is an axonally secreted serpin that is involved in regulating plasminogen and its enzyme activators, such as tissue plasminogen activator (tPA). The protein has been increasingly shown to play key roles in neuronal development, plasticity, maturation and synaptic refinement. The proteinase inhibitor may function both independently and through tPA-dependent mechanisms. Herein, we discuss the recent evidence regarding the role of neuroserpin in healthy and diseased conditions and highlight the partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 189 publications
(343 reference statements)
0
10
0
Order By: Relevance
“…They are involved in calcium homeostasis. A novel study conducted by Godinez et al (2022) has revealed that neuroserpin plays an important role in mediating neurite outgrowth and axonal development as well as in maintaining normal synaptic plasticity through its inhibitory effects on the tissue plasminogen activator (tPA) in the CNS, thereby preventing tPA interaction with the NMDA receptor-mediated calcium influx, which contributes to excitotoxic neuronal apoptosis. , The elevated expression of serpin superfamily proteins was associated with low survival and increased recurrence rates …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are involved in calcium homeostasis. A novel study conducted by Godinez et al (2022) has revealed that neuroserpin plays an important role in mediating neurite outgrowth and axonal development as well as in maintaining normal synaptic plasticity through its inhibitory effects on the tissue plasminogen activator (tPA) in the CNS, thereby preventing tPA interaction with the NMDA receptor-mediated calcium influx, which contributes to excitotoxic neuronal apoptosis. , The elevated expression of serpin superfamily proteins was associated with low survival and increased recurrence rates …”
Section: Discussionmentioning
confidence: 99%
“…141 Based on our findings, we can suggest other straightforward therapeutic strategies to counteract the growth of IDH mutant high-grade gliomas, such as inhibition of the neuroserpin effect, which mediates in correlation with p63, tumor growth, metastasis, and cellular survival; likewise, the activation of the plasmin proteolytic axis was involved in multiple metastaticsuppressive mechanisms, in particular, degradation of the axonal path-finding L1 cell-adhesion molecule (L1CAM) specifically expressed by metastatic cancer cells during their invasion of the brain parenchyma and capillaries. 95 Moreover, the increased expression of cystatins involved in apoptosis regulation elicited by oxidative stress is an attempt to counteract the autolytic properties of cathepsin(s). Thus, disturbing the balance between cystatin and cathepsin with targeted therapy can promote tumor cell death.…”
Section: Therapy Target Pathways For Human Idh Mutant High-grade Gliomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Markedly, neuroserpin polymorphism and dysfunction trigger its intracellular accumulation with the development of wide-spectrum diseases like familial encephalopathy with neuroserpin inclusion body (FENIB) [ 69 ]. Alterations in the expression and activity of neuroserpins are associated with the development of different neuropathological disorders.…”
Section: Neuroserpin In Admentioning
confidence: 99%
“…Genetic variations of neuroserpin expression are linked with the development of various neurological disorders, including FENIB, myoclonic epilepsy, AD, cancer, and glaucoma (Fig. 5 ) [ 69 ].
Fig.
…”
Section: Neuroserpin In Admentioning
confidence: 99%